Enhancing Dodol Micro, Small, And Medium Enterprises (MSMEs) Performance In Garut District: The Impact Of Entrepreneurial Orientation - Lindayani, Lindayani; Solihat, Asri; Rahmawati, Rena (Entrepreneurship Faculty, Universitas Garut, 2023)
Micro, small, and medium enterprises significantly influence economic growth and development. The findings of this study indicate that innovation, risk-taking, and proactiveness are crucial dimensions of entrepreneurial orientation that positively impact the performance of MSMEs in the Garut Regency. The primary objective of this research is to assess the influence of entrepreneurial orientation on the performance of Dodol micro, small, and medium enterprises (MSMEs) in the Garut Regency, focusing specifically on entrepreneurs engaged in Dodol businesses. Conducted as quantitative research with a descriptive approach, the study involves a population of Dodol business actors in the Garut Regency. A sample of 81 respondents was selected through simple random sampling techniques and analyzed with SPSS statistics 21. The research employs various analytical tools, including simple linear regression, instrument testing, classical assumption testing, and hypothesis testing. The research reveals that the entrepreneurial orientation variable has a substantial influence of 44.6% on the performance of MSMEs. In conclusion, this study underscores the critical importance of enhancing the performance of MSMEs, emphasizing the necessity of understanding the entrepreneurial orientation of a company as integral to achieving this goal.